Marketing Strategy for Murabahah Financing Products for Micro Enterprises Using SWOT Analysis and Business Model Canvas Method (Case Study on BPRS Al-Washliyah Medan Krakatau) - Astri, Afiyah Dwi; Syahbudi, Muhammad; Maidalena, Maidalena (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze the marketing strategy of Murabahah financing products in micro businesses implemented by BPRS Al-Washliyah Medan Krakatau. Using a qualitative approach with a case study method, data was obtained through in-depth interviews, observations, and documentation. The analysis was carried out using the SWOT model and Business Model Canvas (BMC). The results of the study indicate that BPRS has internal strengths in the form of sharia principles, community networks, and fast service, with external opportunities from increasing interest in sharia financing and the growth of MSMEs. The marketing strategy is focused on a personal, educational approach, and the use of social media, although it still faces challenges such as low sharia financial literacy and limited human resources. Despite a decrease in the number of accounts, the nominal financing remains high, reflecting an increase in the quality of fund distribution. The study concludes that the success of the marketing strategy depends on optimizing human resources, digitizing services, and strengthening sharia values in facing modern financial competition.